Design and Simulation of a PLC-Based Cold Storage Temperature Control System for Agricultural Product Storage - Batara Manggala Sianturi; Beni Satria; Ahmad Dani (Jurnal Info Sains : Informatika dan Sains, 2026)
Horticultural products require storage at temperatures ranging from 0–10 °C to maintain post-harvest product quality. Cold storage is an effective solution because it can maintain temperature stability, which affects the rate of respiration, microbial activity, and the shelf life of products. However, conventional cold storage systems that use only a single compressor are less flexible in adjusting to thermal loads, which reduces efficiency, accelerates component wear, and decreases the overall reliability of the system. This study designs and simulates an automatic temperature control system based on a Programmable Logic Controller (PLC) by regulating two compressor units according to room temperature and integrating the principles of hysteresis, staging, and rotation. The system uses an upper temperature limit of 10 °C, a lower temperature limit of 0 °C, and a hysteresis point at 5 °C as a reference for changing operating modes. Compressors can operate simultaneously to speed up cooling, compressors can operate alternately to balance the load while maintaining optimal temperature, and compressors can stop simultaneously to stop cooling and prevent product freezing. The simulation was carried out using CX-Programmer for ladder logic and CX-Designer for Human Machine Interface (HMI) visualization. Testing involves temperature variations above 10 °C, in the range of 0–10 °C, and below 0 °C to verify the system's response. The results show that the system is able to maintain the storage room temperature at optimal conditions automatically and stably. The system successfully applied the principles of hysteresis, staging, and rotation effectively in response to temperature changes. The system is also equipped with automatic recovery capabilities that maintain precise control after a power outage. This design has the potential to be applied in food preservation, supply chain logistics, and temperature-sensitive industries, as well as supporting the development of cooling and autonomous systems.